PENGARUH METODE FOOD ART MELALUI PEMBERIAN BUAH PEPAYA TERHADAP NAFSU MAKAN ANAK 1-5 TAHUN DALAM PENCEGAHAN STUNTING DI POSYANDU BUNCIS 2 SIBORONGBORONG - Inriani Tri An Cika Pasaribu; Dior Manta Tambunan (Universitas Murni Teguh, 2026)
Low appetite in children aged 1–5 years can lead to inadequate nutritional intake and increase the risk of stunting. The food art method using papaya is an approach to improve children’s appetite through attractive food presentation. This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of children aged 1–5 years at Posyandu Buncis 2 Siborongborong and it used total sampling technique of 23 children. Appetite data were collected before and after the intervention. Data normality was tested using the Shapiro–Wilk and it showed that the data were not normally distributed and The Wilcoxon test were used as a bivariate data analyzed. The results used Wilcoxon test showed a p-value of 0.000 (p <0.05), indicating a statistically significant difference in appetite before and after the intervention. It is concluded that The food art method using papaya has a significant effect on improving appetite among children aged 1–5 years and can be considered an alternative strategy for stunting prevention. It is recommended that future researchers to add variables such as nutritional status, food preferences, and family environmental conditions.